Familial Alzheimer’s Disease : Oxidative Stress, b-amyloid, Presenilins, and Cell Death (1998)
ABSTRACT : The basic etiology of Alzheimer’s disease remains unknown, although four genes have so far been involved: β-amyloid precursor protein, presenilin-1, presenilin-2 and apolipoprotein E genes. 2. The largest familial Alzheimer’s disease (FAD) kindred so far reported belong to a point mutation in codon 280 that results in a glutamic acid-to-alanine sustitution in presenilin-1 characterized in Antioquia, Colombia. 3. A hypothetical unified molecular mechanism model of cell death in FAD mediated by presenilin-1, β-amyloid, and oxidative stress is proposed as an attempt to explain the mechanisms of neuronal loss in this neurodegenerative disorder.